The effect of diabetes mellitus on the Two‐Step value for gait ability. Issue 3 (8th November 2018) - Kimura, Kazuki; Ninomiya, Hideki; Endo, Yoshiaki; Kambayashi, Yukio
Abstract: Objective: Impaired glucose tolerance is a factor that can affect locomotive syndrome. This study aimed to elucidate the impact of diabetes mellitus (DM) on the value of the Two‐Step Test as an index of gait ability in locomotive syndrome. The present study focused on DM patients who did not have diabetic polyneuropathy (DP) and discussed the effect of DM on the Two‐Step value. Methods: This cross‐sectional study compared the Two‐Step values between DM patients without DP (32 male, 28 female; mean age 62.2 years) and regional residents without DM (25 male, 18 female; mean age 61.8 years). Results: Body mass index was significantly higher in the DM patients than in the regional residents. The Two‐Step value was lower in DM patients than in individuals without DM among females but not among males. Therefore, the Two‐Step value was lower in female DM patients than in female regional residents of the same age. Conclusion: This study presents a new observation: The gait ability in female DM patients can be impaired, even before the development of DP.